Algicidal bacteria trigger contrasting responses in model diatom communities of different composition. Issue 8 (27th February 2019) - Bigalke, Arite; Pohnert, Georg
Abstract: Algicidal bacteria are important players regulating the dynamic changes of plankton assemblages. Most studies on these bacteria have focused on the effect on single algal species in simple incubation experiments. Considering the complexity of species assemblages in the natural plankton, such incubations represent an oversimplification and do not allow making further reaching conclusions on ecological interactions. Here, we describe a series of co‐incubation experiments with different level of complexity to elucidate the effect of the algicidal bacterium Kordia algicida on mixed cultures of a resistant and a susceptible diatom. The growth of the resistant diatom Chaetoceros didymus is nearly unaffected by K. algicida in monoculture, while cells of the susceptible diatom Skeletonema costatum are lysed within few hours. Growth of C. didymus is inhibited if mixed cultures of the two diatoms are infected with the bacterium. Incubations with filtrates of the infected cultures show that the effects are chemically mediated. In non‐contact co‐culturing we show that low concentrations of the lysed algae support the growth of C. didymus, while higher concentrations trigger population decline. Complex cascading effects of algicidal bacteria have thus to be taken into account if their ecological role is concerned. Abstract : This work addresses a central process in plankton community interactions, namely the cascading effect of algicidal bacteria on microalgae in consortia. We show that resistance traits of microalgae become modulated within complex communities and explain previously unpredicted outcomes of phytoplankton infection.